Analysis of body gestures in anger expression and evaluation in android robot. (16th December 2020) - Ajibo, Chinenye Augustine; Ishi, Carlos Toshinori; Mikata, Ryusuke; Liu, Chaoran; Ishiguro, Hiroshi
ABSTRACT: Recent studies in human–human interaction (HHI) have revealed the propensity of negative emotional expression to initiate affiliating functions which are beneficial to the expresser and also help fostering cordiality and closeness amongst interlocutors during conversation. Effort in human–robot interaction has also been devoted to furnish robots with the expression of both positive and negative emotions. However, only a few have considered body gestures in context with the dialogue act functions conveyed by the emotional utterances. This study aims on furnishing robots with humanlike negative emotional expression, specifically anger-based body gestures roused by the utterance context. In this regard, we adopted a multimodal HHI corpus for the study, and then analyzed and established predominant gestures types and dialogue acts associated with anger-based utterances in HHI. Based on the analysis results, we implemented these gesture types in an android robot, and carried out a subjective evaluation to investigate their effects on the perception of anger expression in utterances with different dialogue act functions. Results showed significant effects of the presence of gesture on the anger degree perception. Findings from this study also revealed that the functional content of anger-based utterances plays a significant role in the choice of the gesture accompanying such utterances. GRAPHICAL ABSTRACT: UF0001